Implementasi Metode Hypnoteaching dalam Meningkatkan Motivasi Belajar Santri Studi Kasus Pondok Pesantren An-Nuur Al-Fadhol Banyuwangi - Abdul Rokib; Muhammad Yusron Maulana El-Yunusi (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
The Hypnoteaching method is to permanently and maximally increase students' learning motivation, due to the nature of the subconscious mind that stores a memory of one's mind starting from the womb since the spirit is blown until now. Thus raising a research title "Implementation of the Hypnoteaching Method in Increasing Santri Learning Motivation (Case Study of an-Nuur al-Fadhol Banyuwangi Islamic Boarding School)" with a problem definition whose discussion revolves around pre-induction, induction, deepening, suggestion/ giving suggestions, termination / awakening. As for the limitations of the discussion of learning motivation include: intrinsic motivational factors or within the students and extrinsic motivational factors or from outside the students, all of which need an in-depth study.The purpose of this study is to find out and analyze the Implementation of the Hypnoteaching Method in Increasing Learning Motivation in Santri Pondok Pesantren an-Nuur al-Fadhol BanyuwangiThis study uses qualitative methods, and data collection by interviews, observation, and documentation. The analysis techniques used include: data reduction, data presentation and drawing conclusions.The results of this study can be summed up as follows: First, Improved Santri Learning Motivation at Pondok Pesantren an-Nuur al-Fadhol Banyuwangi can be through two factors, namely intrinsic (inside the students including interests and talents) and extrinsic (outside the students including: support from other people old and the environment).Second, the implementation of the hypnoteaching method in increasing learning motivation in Islamic boarding school students an-nuur al-fadhol Banyuwangi through several stages including: pre-talk, induction, deepening, giving suggestions, and termination (development/normalization).It is hoped that future researchers will conduct more in-depth research on the implementation of the hypnoteaching method in increasing learning motivation in students.